John Dee's conversations with angels cabala, alchemy, and the end of nature - Harkness, Deborah E., 1965- (Cambridge, U.K. ; New York : Cambridge University Press, 1999)
"John Dee (1527-1608/9) was a Cambridge-educated natural philosopher who served Queen Elizabeth I as court astrologer and who wrote works on many subjects including mathematics, alchemy, and astronomy. His most prolonged intellectual project, however, was conversations with angels using a crystal ball and a variety of assistants with visionary abilities. Dee's angel conversations have long puzzled scholars of early modern science and culture, who have wondered how to incorporate them within the broader contexts of early modern natural philosophy, religion, and society. Using Dee's marginal notes in library books, his manuscript diaries of the angel conversations, and a wide range of medieval and early modern treatises regarding nature and the apocalypse, Deborah Harkness argues that Dee's angel conversations represent a continuing development of his natural philosophy. The angel conversations, which included discussions of the natural world, the practice of natural philosophy, and the apocalypse, were conveyed to audiences from London to Prague, and took on new importance within these shifting philosophical, religious, and political situations. When set within these broader frameworks of Dee's intellectual interests and early modern culture, the angel conversations can be understood as an attempt to practice natural philosophy at a time when many thought that nature itself was coming to an end."--Jacket.
Genesis -- The Colloquium of Angels: Prague, 1586 -- Building Jacob's Ladder: The Genesis of the Angel Conversations -- Climbing Jacob's Ladder: Angelology as Natural Philosophy -- Revelations -- "Then Commeth the Ende": Apocalypse, Natural Philosophy, and the Angel Conversations -- "The True Cabala": Reading the Book of Nature -- Adam's Alchemy: The Medicine of God and the Restitution of Nature.
Includes bibliographical references (p. 227-246) and index.
Description based on print version record.
Keywords: Dee, John, -- 1527-1608.; Dee, John, -- 1527-1608.; Kabbala; Alchemie; Engelen; Natuurfilosofie; Dee, John, -- 1527-1608.; BODY, MIND & SPIRIT / Parapsychology / General; Electronic books